The Effectiveness Of The Palermo Protocol In The Case Of Women And Children: Countering Human Trafficking In The Philippines - Wicahyo, Maulidia Zalsa; Perbawani, Firsty Chintya Laksmi (POLITICO, 2024)
Human trafficking, particularly involving women and children, is a serious challenge for the Philippines. As a country with a high rate of child sexual exploitation in East Asia, the Philippines has sought to eradicate this crime through the ratification of the Palermo Protocol, the passage of Republic Act No. 9208 and Republic Act No. 10364, as well as the establishment of the Inter-Agency Council Against Trafficking (IACAT). This study analyzes the effectiveness of the implementation of the Palermo Protocol in the Philippines using the Domestic Salience theory to measure the extent to which international norms have been adopted in domestic policies. The results show that the Philippines successfully improved its law enforcement capacity and obtained Tier 1 status in the Trafficking Victims Protection Act (TVPA) in 2016. However, challenges such as limited resources, corruption, and inter-agency coordination still hinder the effectiveness of anti-trafficking policies. With a national strategy that includes prevention, victim protection, law enforcement, and international partnerships, the Philippines continues to reduce human trafficking. Despite significant progress, the study concludes that policy strengthening through cross-sector coordination, capacity building of law enforcement officials, and expansion of victim rehabilitation services are needed to ensure long-term effectiveness in combating human trafficking.